Sistem E-Learning Berbasis Web Pada SMA Negeri 1 Merangin - Susanti , Eka; Assegaff , Setiawan (LPPM Universitas Dinamika Bangsa, 2022)
Teaching and learning activities at SMAN 1 Merangin have several problems, namely the teaching and learning process in the classroom is lacking due to time constraints and also the media used to deliver the subject matter. Submission of subject matter that is less understood by all students. For example, when the teacher has to deliver material to students, it makes it difficult for students to get the subject matter in full and also students have difficulty getting subject matter when students are not in class and also communication between teachers and students is difficult to realize when outside the classroom due to lack of facilities. interaction and communication between teachers and students. Based on these problems, the authors propose an e-learning system design as a solution to the problems faced. This study uses a tool that is UML in system modeling. The result of this research is the design of an e-learning system prototype that can be implemented in the form of an application at SMAN 1 Merangin as a solution to existing problems.